The Impact of Host Community on Destination (re)branding: A Case Study of Hiroshima. (3rd May 2013) - Wu, Chuntao; Funck, Carolin; Hayashi, Yoshitsugu
ABSTRACT This paper investigates local groups' opinions on interpreting a dark heritage site for the promotion of tourism and analyzes their roles in tourism activities, through a case study of Hiroshima, Japan. As the first city suffered nuclear bombing, Hiroshima is a primary tourism destination in Japan but faced the challenge of revitalization. Fieldwork investigation methods, including semi‐structured interviews, were applied. The results suggest that local people hold favorable attitudes toward tourism development. They conduct an alternative approach to rejuvenating Hiroshima by identifying the essence of the place – a cheerful and peaceful city – and incorporating it into tourism events. Copyright © 2013 John Wiley & Sons, Ltd.